Spin models in three dimensions: adaptive lattice spacing - Hasenbusch, Martin (Physical review. E, Statistical, nonlinear, and soft matter physics, 2015)
Aiming at the study of critical phenomena in the presence of boundaries with a nontrivial shape we discuss how lattices with an adaptive lattice spacing can be implemented. Since the parameters of the Hamiltonian transform nontrivially under changes of the length scale, adapting the lattice spacing is much more difficult than in the case of the numerical solution of partial differential equations, where this method is common practice.
Gesehen am 14.09.2022